The Skull and Cervical Spine Radiographs of Tutankhamen: A Critical Appraisal - Boyer, Richard S.; Rodin, Ernst A.; Grey, Todd C.; Connolly, R. C. (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Tutankhamen, the last pharaoh of the XVIIIth dynasty, died unexpectedly at approximately age 18 years. A cause of death has never been established, but theories that the young king was murdered by a blow to the head have been proposed based on skull radiographs obtained by a team from the University of Liverpool in 1968. We recently had the opportunity to evaluate the skull and cervical spine radiographs of Tutankhamen. The purpose of this study was to report our critical appraisal of the radiographs of Tutankhamen regarding the findings alleged to indicate traumatic death.METHODS: Copies of lateral, anteroposterior, and submental vertex skull radiographs of Tutankhamen were reviewed with special attention to the claims of a depressed skull fracture, intracranial bone fragments, and calcified membrane of a posterior fossa subdural hematoma. A phantom skull was radiographed to reproduce the appearance of the floor of the posterior fossa in the lateral projection.RESULTS: The skull radiographs of Tutankhamen show only postmortem artifacts that are explainable by an understanding of the methods of mummy preservation used at the time of his death. Some findings also relate to trauma inflicted by an autopsy performed in 1925. The alleged calcified membrane of a posterior fossa subdural hematoma is easily reproduced with a skull phantom.CONCLUSION: Our critical review of the skull and cervical spine radiographs of Tutankhamen does not support proposed theories of a traumatic or homicidal death.